Evaluasi Implementasi Program Makan Bergizi Gratis (MBG) Dalam Mendukung Generasi Emas Indonesia 2045 - Nur Aida Kubangun; Riswan Riswan; Rahmat Pannyiwi; Muhammad Asikin; Yudi Muammar (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
ABSTRACT Background: Human resource quality is a key factor in achieving Indonesia Golden Generation 2045. The Free Nutritious Meal Program (MBG) was introduced as a strategic intervention to improve nutritional fulfillment, support child growth, and strengthen educational outcomes. Large-scale nutrition programs require continuous evaluation to ensure effectiveness and sustainability. Objective: This study aimed to evaluate the implementation of the Free Nutritious Meal Program (MBG) in supporting health improvement and human resource development toward Indonesia Golden Generation 2045. Methods: This study used a descriptive evaluative design with a cross-sectional approach. The sample consisted of 100 respondents including beneficiaries, program implementers, and related stakeholders. Data were collected using questionnaires assessing program implementation, food quality, target accuracy, health benefits, and implementation challenges. Data were analyzed using descriptive statistics. Results: The results showed that most respondents assessed MBG implementation as good (72%). Positive aspects included improved access to nutritious food (78%), support for learning concentration (70%), and increased awareness of healthy eating habits (75%). However, several challenges remained, including distribution systems, food quality monitoring, implementer readiness, and evaluation mechanisms. Conclusion: The Free Nutritious Meal Program has strong potential to support Indonesia Golden Generation 2045 through improved nutrition and human resource quality. Optimization requires stronger governance, food safety monitoring, equitable distribution, and continuous evaluation. Keywords: Free Nutritious Meal Program, Program Evaluation, Child Nutrition, Golden Generation 2045, Health Policy